PENGELOLAAN OBJEK WISATA MONKEY FOREST DESA PADANG TEGAL DALAM MASA PANDEMI MELALUI KONSEP COMMUNITY BASED TOURISM - Putri, Dewa Ayu Ambari; Wirantari, I Dewa Ayu Putri; Wijaya, Komang Adi Sastra (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
This study aims to analyze the management of Monkey Forest Tourism Objects during the Pandemic Period through the concept of Community Base Tourism. This research uses descriptive qualitative method. The findings show that in the planning stage this concept has been running well. However, this was not matched by the enthusiasm and knowledge and skills of the people inside and outside of MSW management. At the implementation stage, the implementation of CBT has not run smoothly. There are obstacles such as the addition of attractions which are constrained during the pandemic due to the restrictive policies carried out by the government as well as drastically reduced tourist visits. In the monitoring/evaluation stage, CBT is already good. But on the other hand, during the corona virus pandemic there was a decrease in visitors so that the income from the Monkey Forest Tourism Object also decreased and indirect participation also decreased. Keyword : Community Base Tourism, Tourism, Management, Monkey Forest